Anaerobic digestion of ensiled orange peel waste: Preliminary batch results. (June 2018) - Calabrò, Paolo S.; Panzera, Maria F.
Highlights: Orange peel waste (OPW) production is strictly influenced by its seasonal spread. Ensiling with anaerobic digestion represents a promising option for OPW management. Methane production depends on the ensiling time. An improvement of methane production occurs for OPW ensiled for the longest period. Better results have been registered using also already acclimatised bacteria. Abstract: According to the official data, oranges are one of the most cultivated fruit in the world and the major part of them are used in industrial processes to produce juices, jams and other products. From these processes, huge amounts of residues are produced and among them the most abundant is orange peel waste (OPW). One promising option in the management of OPW is represented by anaerobic digestion for methane production. The aim of this paper is to analyse the effects of ensiling (a form of storage used to overcome the problem of OPW seasonal production) on bio-methane production, also evaluating the influence of bacteria adaptation to the substrate at lab scale. Two sets of batch experiments were carried out, the first evaluated the methane potential of OPW ensiled up to 37 days. The highest production was registered for samples of OPW ensiled for 37 days, with a value of 365 Nml CH4 /g VS. The second set of batch test was aimed at verifying the effect of the adaptation of the inoculum. OPW ensiled for 7 days inoculated with sludge already adapted to the substrate yielded 513.7 Nml CH4 /g VS versus 187.2 Nml CH4 /g VS of the corresponding test using non adapted inoculum.